Spatial distribution patterns and landslide susceptibility analysis from a global–local perspective along the Zhuzhou-Guangzhou section of the Beijing–Guangzhou railway - Liu, Hanxing; Xu, Chong; Feng, Liye; Wang, Peng; Sun, Jingjing; Zhang, Xuewei; Wang, Juanling; Sun, Qihao; Li, Kang (Frontiers in Earth Science, 2026)
The Beijing–Guangzhou Railway is a critical transportation corridor in China, with the Zhuzhou–Guangzhou segment particularly susceptible to landslides due to steep terrain and marked climatic variability. This study combined 713 large-scale landslide remnants with 14 Influencing factors (topography, geology, and hydrology) to analyze landslide spatial distribution and proposed a multiscale landslide susceptibility assessment framework based on a “global modeling–local analysis” approach. The contribution of each factor to susceptibility was quantified using a random forest model coupled with the SHapley Additive exPlanations (SHAP) method. Spatial analysis revealed that landslides are concentrated in areas at 188–752 m elevation, with slopes of 15°–30°, curvatures of −0.35–0.22, Jurassic strata, and high precipitation, and are significantly influenced by river erosion and railway engineering activities. The susceptibility model performed well (AUC = 0.88). Global analysis showed that high and very high susceptibility areas are primarily located in the central and southern sections of the study area, particularly in northern Lechang, Shaoguan, and Suxian District, Chenzhou. Local analysis of three representative sections further indicated that slope, Topographic Wetness Index (TWI), elevation, and curvature are the primary hazard factors, with the order of contribution varying across sections, reflecting the regional characteristics and complexity of landslide mechanisms along the railway. This study provides a scientific basis for landslide risk prevention and control along the Beijing-Guangzhou Railway and a transferable reference for susceptibility assessment in similar regions.